The Impact of Islamic Monetary Policy on Indonesia's Economic Growth - Marpaung, Taufik Arnanda; Imsar; Tambunan, Khairina (Journal of Islamic Economics and Finance Studies, 2023)
Indonesia is a Muslim-majority country with relatively low economic growth. Therefore, the success of monetary policy does not only depend on conventional instruments, but also on Islamic instruments. Islamic monetary policy instruments tend to be more related to real activities and real assets. So that increasing public awareness of Islamic principles will cause the effectiveness of Islamic monetary instruments to become stronger, which will also be followed by increased economic growth. This research aims to determine the effect of PUAS, FASBIS, and SBIS on GDP using secondary data in the form of monthly time series from 2018-2022. Data was collected using the Purposive Sampling technique, with the Quantitative Associative method. The data was processed using Eviews 9 and then analyzed using the VAR VECM method to see the long-term and short-term effects of PUAS, FASBIS, and SBIS on GDP. The results show that there is a two-way causal relationship between PUAS and FASBIS, FASBIS and GDP, SBIS and PUAS, as well as a one-way relationship between GDP and SBIS. There is a significant relationship between SATISFIED and GDP, in the long term. Meanwhile, in the short term, all variables do not have a significant effect on GDP. In the long term, the variable that is strong and dominant in influencing GDP is PUAS and has the largest composition that contributes to the GDP variable. This research provides practical and theoretical implications to increase scientific insight in the field of economics and references in making policy decisions to improve technological infrastructure and regulations that support the development of Sharia financial markets.